Comparative Cough Suppression of Chitosan Crab Extract of Uca tangeri and Dihydrocodeine - Joshua Charles Isirima; Precious Ojo Uahomo (Biology, Medicine, & Natural Product Chemistry, 2023)
Cough is an inmate primitive reflex and acts as a part of the body's immune system to protect against foreign materials from the respiratory tract. This study was done to investigate the cough suppression potential of Uca tangeri. A day before the test, guinea pigs were placed individually in a transparent chamber (60 36 60 cm) for 5 minutes before cough was induced by exposure to 15% citric acid, delivered using an Omron compressor nebulizer (rate of 0.4 ml/minutes and particle size 5?m) for 10 minutes. The animals were then monitored visually within this exposure time for cough; the latency and counts, of which, were taken as the basal values. The animals exhibiting 10 - 20 bouts of cough were selected for the study and fasted overnight but with access to water. The selected animals were randomly allotted to 5 groups (n=5 per group). The animals were treated orally thus: Group 1 was the control group and received 2 ml/kg of normal saline; group 2 received 25 mg/kg dihydrocodeine; Group 3 received 150 mg/kg extract; group 4 received 300 mg/kg extract and group 5 received 600 mg/kg of the extract. An hour after administration, they were re-exposed to citric acid aerosol (as earlier described) and the latency of cough and cough count were recorded. The procedure was repeated at hours 2 and 3 after treatment. Antitussive activity was then evaluated in each guinea-pig as the percentage reduction in the number of coughs also known as percentage suppression of cough and percentage increase in latency of cough. The results revealed that Uca tangeri exhibited a dose dependent percentage increase in cough latency period as well as percentage increase in suppression of cough which was inferior to dihydrocodeine, but significantly greater than normal saline and basal levels.